Exploration of Nakagami fading in ultrawideband wireless channels - Sipal, V; Allen, B; Edwards, D (2011)
This letter explores the parameters m and Ω of the Nakagami distribution for fading in ultrawideband wireless channels. In contrast to the IEEE 802.15.4a model, it shows the dependency of these parameters on bandwidth, which facilitates optimisation of UWB transceiver systems.